Temporal shifts in semen parameters across a major COVID-19 outbreak wave: a retrospective cohort study using epidemiological time-windows - Wang, Hai; Zheng, Xianjue; Pan, Haojie; Zheng, Jiayong; Xu, Zitong (Frontiers in Reproductive Health, 2025)
ObjectiveTo investigate the temporal variations in male semen quality parameters before, during, and after a major regional COVID-19 outbreak wave.MethodsThis retrospective cohort study analyzed initial semen samples collected at our hospital between June 1, 2022, and June 30, 2023. Based on regional epidemiological data corresponding to a major outbreak, participants were stratified into three groups by sample collection date: a pre-outbreak group (Group A, September 1, 2022–December 31, 2022, n = 330), a peak-outbreak group (Group B, January 1, 2023–March 31, 2023, n = 413), and a post-outbreak group (Group C, April 1, 2023–June 30, 2023, n = 480). Conventional semen parameters, sperm acrosin activity, and sperm DNA fragmentation index (DFI) were compared.ResultsThe peak-outbreak group (Group B) showed significantly lower sperm concentration compared to both the pre-outbreak group (49.1 vs. 59.6 × 106/ml, P = 0.009) and the post-outbreak group (49.1 vs. 62.6 × 106/ml, P < 0.001). Similarly, progressive motility was significantly lower in the peak-outbreak group (37.7%) compared to the pre-outbreak (45.1%, P < 0.001) and post-outbreak groups (43.4%, P < 0.001). No significant differences were found in these parameters between the pre-outbreak and post-outbreak groups (P > 0.05). Sperm acrosin activity and DFI remained stable across all three groups (P > 0.05).ConclusionSemen concentration and motility were significantly lower in samples collected during the peak of a major COVID-19 outbreak wave, with parameters returning to pre-outbreak levels in the subsequent 3-month period. Key sperm functional biomarkers, including acrosin activity and DNA integrity, appeared resilient throughout these distinct epidemiological phases.